The Condemnation of Priscillian’s use of non-Canonical Books and his Defense in Tractatus III: Liber de Fide et de Apocryphis - Ferreiro, Alberto (Vox Patrum, 2023)
One of the accusations against Priscillian and his followers was their use of non-canonical books in their writings and teachings. This was proof positive for Priscillian’s opponents that he and his followers were a sect worthy of condemnation and that their writings were tainted with heresy. These accusations are found in several of the Suevic-Visigothic councils of Hispania. it is fortuitous that we have Priscillian’s response to this accusation in his Tractatus III: Priscilliani Liber de Fide et de Apocryphis. In this work Priscillian wrote a spirited and proficient defense against his adversaries.